Clinical Anastomotic Leakage After Rectal Cancer Resection Can Be Predicted by Pelvic Anatomic Features on Preoperative MRI Scans: A Secondary Analysis of a Randomized Controlled Trial. Issue 11 (November 2019) - Ma, Tenghui; Zhong, Qinghua; Cao, Wuteng; Qin, Qiyuan; Meng, Xiaochun; Wang, HuaiMing; Wang, Jianping; Wang, Lei
Abstract : BACKGROUND: We demonstrated previously that radiation proctitis induced by preoperative radiotherapy is a predisposing factor for clinical anastomotic leakage in patients undergoing rectal cancer resection. Quantitative measurement of radiation proctitis is needed. OBJECTIVE: This study aimed to quantitate the changes of anatomic features caused by preoperative radiotherapy for rectal cancer and evaluate its ability to predict leakage. DESIGN: It was a secondary analysis of a randomized controlled trial (NCT01211210). MRI variables were retrospectively assessed. SETTINGS: The study was conducted in the leading center of the trial, which is a tertiary GI hospital. PATIENTS: Patients undergoing preoperative chemoradiation with sphincter-preserving surgery were included. MAIN OUTCOME MEASURES: Anatomic features were measured by preradiotherapy and postradiotherapy MRI. Univariate analyses were used to identify prognostic factors. Receiver operating characteristic curves were constructed to determine the cutoff value of the changes of MRI variables in predicting leakage. RESULTS: Eighteen (14.4%) of the 125 included patients developed clinical anastomotic leakage. Baseline characteristics were comparable between leakage group and nonleakage group. Relative increments of width of presacral space, thickness of rectal wall, and distal end of sigmoid colon discriminate between the 2 groups better than random chance. Relative increments of width of presacral space was the best performing predictor, with area under the curve of 0.722, sensitivity of 66.7%, specificity of 72.0%, and positive and negative predictive value of 28.6% and 92.8%. LIMITATIONS: The study was limited by its small sample size and retrospective design. CONCLUSIONS: Increments of the width of the presacral space, thickness of rectal wall, and distal part of the sigmoid colon helps to identify individuals not at risk for clinical anastomotic leakage after rectal cancer resection. The first variable is the strongest predictor. Changes of these variables should be taken into consideration when evaluating the application of defunctioning stoma. See Video Abstract at http://links.lww.com/DCR/B23 . Clinical Trials Identifier: NCT1211210. LAS FUGAS ANASTOMÓTICAS CLÍNICAS DESPUÉS DE LA RESECCIÓN DEL CÁNCER DEL RECTO PUEDEN PREDECIRSE POR LAS CARACTERÍSTICAS ANATÓMICAS PÉLVICAS EN LAS IMAGENES DE RESONANCIA MAGNÉTICA PREOPERATORIA: UN ANÁLISIS SECUNDARIO DE UN ESTUDIO CONTROLADO ALEATORIZADO: ANTECEDENTES: Anteriormente demostramos que la proctitis inducida por la radiación de radioterapia preoperatoria es un factor predisponente para la fuga anastomótica clínica en pacientes sometidos a resección de cáncer rectal. Es necesaria la medición cuantitativa de la proctitis por radiación. OBJETIVO: Este estudio tuvo como objetivo cuantificar los cambios en las características anatómicas causados por la radioterapia preoperatoria para el cáncer de recto y evaluar su capacidad para predecir las fugas anastomoticas. DISEÑO: Fue un análisis secundario de un estudio controlado aleatorio (NCT01211210). Los variables de imagines de resonancia magnetica se evaluaron retrospectivamente. MARCO: Se llevó a cabo en el centro principal del estudio, que es un hospital gastrointestinal terciario. PACIENTES: Se incluyeron pacientes sometidos a quimiorradiación preoperatoria con cirugía conservadora del esfínter. RESULTADO PRINCIPAL MEDIDO: Las características anatómicas se midieron mediante imagines de resonancia magnetica previa y posterior a la radioterapia. Se utilizaron análisis univariados para identificar los factores pronósticos. Las curvas de características operativas del receptor se construyeron para determinar el valor de corte de los cambios de los variables de resonancia magnetica en la predicción de fugas. RESULTADOS: Dieciocho (14.4%) de los 125 pacientes incluidos desarrollaron fugas anastomóticas clínicas. Las características basales fueron comparables entre el grupo de fugas y el grupo de no fugas. Los incrementos relativos del ancho del espacio presacro, el grosor de la pared rectal y distal del colon sigmoide discriminan entre los dos grupos mejor que la posibilidad aleatoria. Los incrementos relativos del ancho del espacio presacro fueron el mejor pronóstico con un AUC de 0.722, sensibilidad del 66.7%, especificidad del 72.0%, valor predictivo positivo y negativo del 28.6% y 92.8%. LIMITACIONES: Estaba limitado por el tamaño de muestra pequeño y el diseño retrospectivo. CONCLUSIONES: Los incrementos en el ancho del espacio presacro, el grosor de la pared rectal y la parte distal del colon sigmoide ayudan a identificar a las personas que no tienen riesgo de fuga anastomótica clínica después de la resección del cáncer rectal. La primera variable es el predictor más fuerte. Los cambios de estos variables deben tenerse en cuenta al evaluar la aplicación del estoma para desvio. Vea el Resumen del Video en http://links.lww.com/DCR/B23 .